Stroke Patient Communication Tool with Touch Sensor and Phrase Time Step - Aji Pratama, Fajar; Safitri, Meilia; Loniza , Erika; Probo Santoso, Henry (Journal of Fuzzy Systems and Control, 2024)
The purpose of this prototype is to enhance communication between stroke patients and their caregivers, as difficulty in understanding the nuanced wishes of stroke patients often leads to a reduced quality of life for the patients and increased caregiver depression. This study aimed to address these challenges by providing a more effective means of interpreting the desires of stroke patients during their interactions with their caregivers. The prototype utilizes a dual-input system to capture the intricate communication dynamics. The first input involves recording the finger movements of the patient through touch interaction with the TTP223 touch sensor area. In contrast, the second input comprises a time-step phrase that serves as a complementary mechanism for selecting communication phrases. The combination of these inputs is processed using Boolean logic, specifically employing basic AND logic, in which both inputs must register as high to yield a correspondingly high output. The ESP32 microcontroller processes the output signal, and the resulting information is displayed on both an LCD screen and a dedicated Telegram application. The prototype achieved a notable accomplishment of 100% accuracy in reading inputs.